ANALISIS KANDUNGAN GLIKOGEN PADA HATI, OTOT, DAN OTAK HEWAN: (Analysis Of Glicogen Content On Heart, Muscle, And Animal Brain) - fatmawati mustakim; Mulyati M Tahir (Hasanuddin University Food Science and Technology Study Program, 2019)
Glycogen is the main type of stored carbohydrate found in animals. Glycogen is formed as excess glucose deposits in the body which are used as energy reserves. The purpose of this analysis is to find out the procedure for glycogen extraction and to determine the glycogen content in some food ingredients. The method used in this lab is iodine extraction and testing. The materials used in this lab are TCA, ethanol, NaCl, iodine, chicken liver, beef liver, beef brain, beef, and chicken meat. The results obtained in this lab, namely chicken liver after adding iodine to brownish orange, beef liver brown, chicken meat brown, beef brown, and brown brains clear brown and highest rendemen levels, namely in the liver of cattle by 55% and the lowest is found in the brains of cattle, which is equal to 0% The yield in cattle is 0%. The conclusions obtained from this analysis are that the procedure for extracting glycogen was carried out using several solvents and samples of chicken liver produced a yield of 32.64%, beef liver by 55%, chicken meat at 9.5%, beef at 29.80%, and cow's brain by 0%.